Curriculum Management Strategies and Effective Implementation of Universal Basic Education in Nigeria - Nimota Jibola Kadir Abdullahi (Profesi Pendidikan Dasar, 2022)
The main goal of this research was to investigate how curriculum management strategies affected the successful implementation of Universal Basic Education (UBE). A total of 712 participants were chosen using proportional random sampling from the sampled primary and junior secondary schools in North-west, Nigeria. Pearson product-moment correlation coefficient and linear regression analysis were used to test the hypotheses. The findings of the study demonstrated that students’ mastery goals, effective classroom instruction, and evaluation all helped to improve the effectiveness of UBE implementation. Thus, it was recommended that school managers should  encourage students' mastery goals so as to help learners to be better engaged in the learning process. Likewise, school managers should strive to create effective classroom instruction to help in engaging learners with concepts and processes of learning. Furthermore, evaluation of curriculum and learners’ activities should be done frequently in order to determine learners’ competence before, during, and after instruction toward effective implementation of the curriculum. The results showed that the curriculum management strategies had a significant impact on the effective implementation of UBE